Peeling of Long, Straight Carbon Nanotubes from Surfaces - Kane M. Barker; Mark A. Poggi; Leonardo Lizarraga; Peter T. Lillehei; Aldo A. Ferri; Lawrence A. Bottomley (Journal of Nanotechnology)
The adhesion of long, straight, single-walled carbon nanotubes to surfaces is examined using multidimensional force spectroscopy. We observed characteristic signatures in the deflection and frequency response of the cantilever indicative of nanotube buckling and slip-stick motion as a result of compression and subsequent adhesion and peeling of the nanotube from the surface. The spring constant and the elastic modulus of the SWNT were estimated from the frequency shifts under tension. Using elastica modeling for postbuckled columns, we have determined the static coefficient of friction for the SWNT on alkanethiol-modified gold surfaces and showed that it varies with the identity of the monolayer terminal group.